Peningkatan Keterampilan Menulis Teks Petunjuk melalui Media Gambar Berseri pada Kelas 2 SD Supriyadi 02 Semarang - Ulwiyatus Sa’adah, Rina; Azizah, Mira; Prima Artharina, Filia; Puji Rahayu, Lilik (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the writing skills of procedural texts among second-grade students at SD Supriyadi 02 Semarang through the use of picture series media. This research is a classroom action research (CAR) conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. Data collection techniques included observation, interviews, written tests, and documentation. The results showed that in the pre-cycle stage, only 18% of students achieved the minimum mastery criteria, which increased to 40% in the first cycle. After implementing the picture series media in the second cycle, student mastery significantly increased to 85%. The picture series media proved effective in helping students understand the sequence of steps visually, thereby facilitating the construction of logical and systematic sentences. In addition to improving learning outcomes, the use of this media also enhanced students’ motivation and engagement during the learning process. Therefore, picture series media is effective in improving procedural text writing skills among lower grade students in elementary school.